Effect of LAMA4 on Prognosis and Its Correlation with Immune Infiltration in Gastric Cancer. (10th August 2021) - Wang, Mingming; Li, Changzheng; Liu, Ying; Wang, Zuomin
Abstract : Background . Laminin alpha 4 (LAMA4) is widely distributed in the basement membranes of various tissues. It can regulate cancer cell proliferation and migration. We investigated the effects of LAMA4 in gastric cancer (GC). Methods . LAMA4 expression patterns were analyzed in GC using the Gene Expression Omnibus (GEO), Gene Expression Profiling Interactive Analysis (GEPIA), and UALCAN. Correlations between LAMA4 expression and clinicopathological characteristics were evaluated using data from The Cancer Genome Atlas (TCGA). The survival analysis was examined using the Kaplan-Meier plotter and GEPIA and ascertained by multivariate Cox analysis. Genetic alterations and DNA methylation of LAMA4 were analyzed using cBioPortal and MethSurv. LinkedOmics was applied to identify coexpressed genes of LAMA4. The association between LAMA4 and infiltration of immune cells was explored using Tumor Immune Estimation Resource (TIMER) and GEPIA. Results . LAMA4 was highly expressed in GC, and its upregulation significantly correlated with T classification (P = 0.040 ). LAMA4 expression was an independent risk factor for overall survival (OS, P = 0.033 ). Patients with genetic alterations of LAMA4 showed a significantly better disease-free survival (DFS, P = 0.022 ). Ten CpG sites of LAMA4 were significantly associated with prognosis in GC. The functions of LAMA4 and coexpression genes were mainly involved in extracellular matrix (ECM) receptor interaction. LAMA4 expression significantly correlated with infiltration of macrophages (P < 0.001 ), CD4+ T cells (P < 0.001 ), and dendritic cells (P < 0.001 ). Furthermore, LAMA4 expression was significantly associated with markers of M2 and tumor-associated macrophages (TAMs). Conclusion . LAMA4 expression was linked to GC prognosis and immune cell infiltration, indicating its potential use as a prognostic biomarker and therapeutic target.